Multikultural Pada Masa Khulafaurrasyidin - Muhammad Asri; Meyniar Albina (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Recruitment  This research aims to examine and analyze the application of the multicultural concept during the period of the Khulafaur Rasyidin, focusing on the policies implemented by the caliphs in addressing the diversity of the society under their leadership. The study explores the social, political, and religious aspects that shaped the multicultural approach during this era, as well as its implications on the life of the diverse society. The research adopts a library reseacrh method. Data was collected through literature study from various primary and secondary sources, including Islamic historical texts and related scholarly works. The findings indicate that the policies of the Khulafaur Rasyidin, such as religious tolerance, equitable power distribution, and respect for local cultures, demonstrated effective implementation of multicultural principles, although challenges existed. This study contributes to understanding how pluralism can be wisely managed within the context of power.